2009
DOI: 10.1177/159101990901500201
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Giant Intracranial Aneurysms

Abstract: We report on report the clinical outcome obtained in treatment of giant intracranial aneurysms (GAs). Between 2005 and 2007, 51 patients with 51 GAs presented at our hospital. Twenty-nine were treated with primary parent vessel occlusion without distal bypass and ten underwent treatment preserving the parent artery. Twelve patients could not be treated endovascularly. Selective embolization (including two remodeling techniques and two stent-coil embolizations) resulted in only one cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Malisch et al 20 found a 33% recanalization rate in giant aneurysms that were part of their study in 1997. The overall rate of aneurysm recanalization after coil embolization may be significantly higher in giant and very large aneurysms compared with smaller lesions [21][22][23] . Regrowth of the aneurysm, coil compaction, and coil migration into soft intra-aneurysmal thrombus are possible explanations for the faster recanalization 20 .…”
Section: Angiographic Follow-upmentioning
confidence: 96%
“…Malisch et al 20 found a 33% recanalization rate in giant aneurysms that were part of their study in 1997. The overall rate of aneurysm recanalization after coil embolization may be significantly higher in giant and very large aneurysms compared with smaller lesions [21][22][23] . Regrowth of the aneurysm, coil compaction, and coil migration into soft intra-aneurysmal thrombus are possible explanations for the faster recanalization 20 .…”
Section: Angiographic Follow-upmentioning
confidence: 96%
“…VBA dissecting aneurysms are rare and challenging diseases with a high associated morbidity and mortality. The pathogeneses of VBA dissecting aneurysms seems to be fibro-muscular dysplasia in patients less than 40 years in age and hypertension in patients more than 40 years in age (15,16). There is a hypertension history in patients more than 40 years in age and no head trauma history in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the Pcomas proved to be a good predictor of the ability to tolerate BA occlusion. Basilar artery or bilateral VA occlusion might be considered appropriate treatment in the event of recurrent or progressive enlargement of the BA aneurysm, provided that the patient's Pcomas would provide demonstrably ample collateral flow (16,29). Balloon test occlusion may be of benefit to determine if the collateral circulation is limited anatomically or compromised by vasospasm (11).…”
Section: Discussionmentioning
confidence: 99%
“…For patient consulting it will be clear to ask different reference centers in Europe what to do after finding an intracranial vascular malformation not in an acute stage (other opinions, expertise, complication rate, risk factors etc.). The interdisciplinarity and a particular knowledge of the devices and material is mandatory for the career of neurointerventionalists 16,19,20 .…”
Section: Economymentioning
confidence: 99%